2016
DOI: 10.1016/j.redox.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase pi modulates NF-κB activation and pro-inflammatory responses in lung epithelial cells

Abstract: Nuclear Factor kappa B (NF-κB) is a transcription factor family critical in the activation of pro- inflammatory responses. The NF-κB pathway is regulated by oxidant-induced post-translational modifications. Protein S-glutathionylation, or the conjugation of the antioxidant molecule, glutathione to reactive cysteines inhibits the activity of inhibitory kappa B kinase beta (IKKβ), among other NF-κB proteins. Glutathione S-transferase Pi (GSTP) is an enzyme that has been shown to catalyze protein S-glutathionylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 40 publications
4
51
0
1
Order By: Relevance
“…For example, glutaredoxins (GRX), known for their ability to deglutathionylate proteins [18, 73], can also catalyze the reverse reaction in the presence of excess GSSG, but this would again require dramatic changes in GSH:GSSG ratios to allow for this reaction to go in the reverse direction. It has similarly been suggested [26] that glutathione S -transferase π 1 (GSTP1), an enzyme that was recently found to catalyze S -glutathionylation of various target proteins [74], might do so by utilizing GSSG. GSTP has a number of domains important to its function, including a G domain is important for the activation of GSH and an H-domain important in its ligandin (protein-protein interaction) function [75].…”
Section: Chemical Detection Of Sulfenic Acid: Is It In Fact Sulfenmentioning
confidence: 99%
“…For example, glutaredoxins (GRX), known for their ability to deglutathionylate proteins [18, 73], can also catalyze the reverse reaction in the presence of excess GSSG, but this would again require dramatic changes in GSH:GSSG ratios to allow for this reaction to go in the reverse direction. It has similarly been suggested [26] that glutathione S -transferase π 1 (GSTP1), an enzyme that was recently found to catalyze S -glutathionylation of various target proteins [74], might do so by utilizing GSSG. GSTP has a number of domains important to its function, including a G domain is important for the activation of GSH and an H-domain important in its ligandin (protein-protein interaction) function [75].…”
Section: Chemical Detection Of Sulfenic Acid: Is It In Fact Sulfenmentioning
confidence: 99%
“…This transition is largely mediated through changes in IκB phosphorylation and protein turnover . Glutathione has been shown to modulate NF‐κB signaling, both positively and negatively, through multiple mechanisms, including changes in the quantity and redox ratio of glutathione, activation of glutathione peroxidase, and by glutathionylation of IκB kinases (IKKs), IκB, or NF‐κB subunits . Our finding that 50 kPa cyclic loading increased GSH while also lowering the ratio of GSH:GSSG raises questions about how glutathione may contribute to altered NF‐κB signaling.…”
Section: Discussionmentioning
confidence: 87%
“…18 Glutathione has been shown to modulate NF-kB signaling, both positively and negatively, through multiple mechanisms, including changes in the quantity and redox ratio of glutathione, activation of glutathione peroxidase, and by glutathionylation of IkB kinases (IKKs), IkB, or NF-kB subunits. [31][32][33] Our finding that 50 kPa cyclic loading increased GSH while also lowering the ratio of GSH: GSSG raises questions about how glutathione may contribute to altered NF-kB signaling. Interestingly, the finding that 100 mM of tBHP pre-treatment reduced the acute effects of mechanical stress on cell death and proteoglycan catabolism 22 may be mediated in part through altered NF-kB signaling.…”
mentioning
confidence: 99%
“…Recently, Tew and Janssen-Heininger and their colleagues have demonstrated that glutathione S-transferase π (GSTP) can glutathionylate IKKβ with GSSG, and thereby activate NF-κB [40]. This process requires a source of GSSG, which is likely to be a GPx or Prdx6 closely associated with the target protein, so that a relatively high concentration of GSSG is present in the immediate location.…”
Section: Enzymatic Disulfide Formation In Signaling Proteinsmentioning
confidence: 99%